The Effect of Product Quality and Service Quality on Customer Satisfaction in Restaurants at Medan City - Lidya Kesuma Sari (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to examine the effect of product quality and service quality on customer satisfaction in restaurants. Product quality refers to the attributes of food such as taste, freshness, portion, and presentation, while service quality covers aspects like responsiveness, reliability, assurance, and empathy in service delivery. The research employs a quantitative method using a structured questionnaire distributed to 120 restaurant customers in a major urban area. The data were analyzed using multiple linear regression with SPSS software to determine the influence of the independent variables on customer satisfaction. The results reveal that both product quality and service quality have a positive and significant effect on customer satisfaction, with product quality showing a slightly stronger impact. This indicates that although the quality of service contributes to the overall dining experience, customers still prioritize the quality of the food itself. The findings support prior research suggesting that food excellence and service interactions are key determinants of satisfaction in the food service sector. The study contributes to marketing and service management literature by reinforcing the importance of maintaining high product and service standards to enhance satisfaction and customer loyalty. It also provides managerial implications for restaurant operators to focus not only on food preparation consistency but also on staff training to deliver excellent service. Future research may incorporate additional variables such as restaurant ambiance, perceived price fairness, and brand image as potential mediating or moderating factors influencing customer satisfaction.